The Permissive Method in the Education of the Prophet Muhammad SAW to strengthen students' understanding - Syahrul Syahrul (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This article examines the exemplary method (tamsil) in the education of the Prophet Muhammad PBUH as an effective strategy in strengthening students' understanding of Islamic values. Exemplary is understood not just as a rhetorical style, but as a pedagogical approach that bridges abstract concepts with students' concrete experiences. This study uses a qualitative method with a literature study approach, analyzing two hadiths narrated by Imam Muslim that display the example of the Prophet: about the reader of the Qur'an and about the influence of association. The results of the study show that the examples used by the Prophet are contextual, emotional, and communicative, so that they are able to build conceptual and affective understanding at the same time. This method is in harmony with modern learning strategies such as contextual learning and analogical reasoning, and is very relevant to be applied in contemporary Islamic education. Thus, the Prophet's exemplary approach can be an inspiration in designing meaningful and transformative learning strategies.